Pre-Service Secondary Mathematics and Physics Teachers’ Perceptions on Educational Research - Tamba, Kimura Patar; Sitompu, Henni (FKIP Universitas Lampung, 2022)
Educational research is very important in improving the quality of learning practices. The purpose of this research is to describe and analyze pre-service teachers' perspectives on educational research. This research is a quantitative research using survey method in collecting data. Data was collected from 39 pre-service secondary teachers, consisting of majors in mathematics education and physics education. The data collection instrument used was a questionnaire. Data analysis consisted of descriptive statistics and Pearson moment-product correlation test. The results showed that pre-service teachers' perspectives on the value of educational research were in the high category. In addition, the results of the study show that there is a significant positive correlation between the value of pre-service teachers' educational research aspects and the teacher's own involvement in research. Keywords: educational research, perspective on research, pre-service teacher DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1635-1643